2015
DOI: 10.1083/jcb.201407065
|View full text |Cite
|
Sign up to set email alerts
|

Tau reduction prevents Aβ-induced axonal transport deficits by blocking activation of GSK3β

Abstract: Tau ablation, knockdown, and reconstitution studies in primary mouse neurons show that tau enables amyloid β oligomers to inhibit axonal transport through activation of GSK3β and through functions of tau that do not depend on its microtubule binding activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 95 publications
11
94
1
Order By: Relevance
“…Ab-Mediated Synaptic Dysfunction by Eg5 Inhibition functions (reviewed in Mucke and Selkoe, 2012), including membrane trafficking (Umeda et al, 2015;Vossel et al, 2015). Accordingly, a recent study found that tau can also inhibit Eg5 activity; thus, Ab may inhibit Eg5 not only directly but also indirectly via regulation of tau (Bougé and Parmentier, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ab-Mediated Synaptic Dysfunction by Eg5 Inhibition functions (reviewed in Mucke and Selkoe, 2012), including membrane trafficking (Umeda et al, 2015;Vossel et al, 2015). Accordingly, a recent study found that tau can also inhibit Eg5 activity; thus, Ab may inhibit Eg5 not only directly but also indirectly via regulation of tau (Bougé and Parmentier, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that alterations in synaptic mitochondria develops earlier than in non-synaptic mitochondria [87]. It seems that tau is required for Aβ-induced impairment of axonal transport, which process is presumably initiated via the activation of NMDARs, glycogen synthase kinase 3β (GSK3β), and casein kinase 2 (CK2) [84,88,89]. Naturally, the above detailed three main aspects of mitochondrial dysfunction act synergistically: the activation of Drp1 and Fis1 by free radicals resulted in mitochondrial fragmentation, their altered synaptic transport, and consequentially reduced synaptic ATP levels and dysfunction [87].…”
Section: Mitochondrial Disturbances In Alzheimer's Diseasementioning
confidence: 99%
“…While our work provides evidence that tau knockdown impairs learning and memory in wild‐type mice, a vast number of studies have shown that knockout of endogenous tau in AD mouse models protects against Aβ‐induced cognitive deficits (Ittner et al., 2010; Ke et al., 2012; Roberson et al., 2011; Vossel et al., 2015). For example, crossing APP mice with tau knockout mice improved spatial reference memory (Roberson et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the Tet/U6 included seven Tet operator sequences. Notably, the ShRNA sequence for tau was obtained from a previous publication (Vossel et al., 2015). The experimental virus was generated to target the MAPT gene through the usage of a doxycycline‐inducible ShRNA.…”
Section: Methodsmentioning
confidence: 99%